Carbonic anhydrase modulation of emotional memory. Implications for the treatment of cognitive disorders - Patrizio Blandina; Gustavo Provensi; Maria Beatrice Passani; Clemente Capasso; Claudiu T. Supuran (Taylor & Francis Group, 2020)
Carbonic anhydrases (CAs, EC 4.2.1.1) are metalloenzymes which use CO2 as substrate, catalysing its interconversion to bicarbonate and a proton. In humans 15 CAs are expressed, 12 of which are catalytically active: the cytosolic CA I-III, VII, XIII, the membrane-bound CA IV, the mitochondrial CA VA and VB, the secreted CA VI, and the transmembrane CA IX, XII, XIV. Nine isoforms are present in the mammalian brain. Evidence supporting that CA inhibitors impair memory in humans has come from studies on topiramate and acetazolamide during acute high-altitude exposure. In contrast, administration of CA activators in animal models enhances memory and learning. Here we review the involvement of selective CA inhibition/activation in cognition-related disorders. CAs may represent a crucial family of new targets for improving cognition as well as in therapeutic areas, such as phobias, obsessive-compulsive disorder, generalised anxiety, and post-traumatic stress disorders, for which few efficient therapies are available.